Evangelical Christianity and democracy in Africa - Ranger, T. O. (Terence O.); Oxford eBooks (Oxford : Oxford University Press, 2008)
One of four projected volumes to emerge from a massive Pew-funded study that sought to answer the question: What happens when a revivalist religion based on scriptural orthodoxy participates in the volatile politics of the Third World? This book considers the case of Africa.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Evangelicalism -- Political aspects -- Africa, Sub-Saharan.; Democracy -- Religious aspects -- Christianity; Christianity and politics -- Africa, Sub-Saharan.; Electronic books